SAT0353 Geographical differences in psoriatic arthritis: a transatlantic comparison. (12th June 2018) - Üreyen, S.B.; Solmaz, D.; Kimyon, G.; Gunal, E.K.; Dogru, A.; Bayindir, O.; Dalkiliç, E.; Ozisler, C.; Can, M.; Akar, S.; Cetin, G.Y.; Tarhan, E.F.; et al.
Abstract : Background: The environmental and genetic factors play a crucial role in the pathogenesis of psoriatic arthritis (PsA) which may cause a difference in disease characteristics for patients from different geographical regions. Objectives: The aim of the study was to explore the disease characteristics, treatment choices and comorbidities in patients with PsA in different countries to see the impact of geographic factors. Methods: PsArt-ID (Psoriatic Arthritis- International Database) is a prospective, multicentre registry in PsA, which was initially developed in Turkey in 2014, with participation of Canada since 2015 and Italy since 2017. Patients with PsA are consecutively registered to this registry with the aim of investigating the real-life data. Patient characteristics across Turkey (n=1283) and Canada (n=119) are compared for this analysis. Results: Canadian patients were older at the time of recruitment (Table). They also were more frequently smokers, had higher duration of education and higher BMI than patients in Turkey. Patients in Canada had more frequent polyarthritis (66.7% vs 39.6%, p<0.001), DIP joint disease (34.2% vs 16%, p<0.001), dactylitis (38.1% vs 29%, p=0.037) nail involvement (55.9% vs 45.7%, p=0.008) and higher number deformed joints (29.3% vs 20.7%, p=0.035) whereas Turkish patients had oligoarthritis more often (37.6% vs 24.8%, p=0.016). For disease activity, tender and swollen joint counts were similar for whereas the skin activity was higher in Turkish patients. There were no major differences between countries regarding treatment choices with similar frequencies of patients on biologic therapies (34.5% vs 30.2%, p=0.339) (figure 1). Although the numbers were very low, there was more frequent cancer in Canada than Turkey (4.3% vs 1.4%, p=0.022) whereas all the other comorbidities were similar. Conclusions: Geographical differences have impacts on the disease features in PsA, which may be due to genetic, environmental and cultural differences. The treatments are comparable suggesting a similar approach by the physicians. Disclosure of Interest: None declared